Between Differences and Continuities: The Liberal Public School System and the Hispano-Catholic Republic in the Colombian Caribbean, 1870-1903 (2024)
Between 1870 and the early 20th century, a series of liberal and conservative governments came to power in Colombia. One of their goals was to establish a modern public school system, with some differences, but also with certain historical continuities. Given the lack of studies in the Colombian Caribbean regarding the implementation of both educational projects, this article analyses the main characteristics of the educational project of radical liberalism and the Regeneration in this part of the national territory, and its role in the process of uniformity of the nation-state in Colombia, particularly in the Caribbean region. With official documentation and a focus on the social history of education, the argument guiding these lines is that the Regeneration did not entail a total dismantling of the governmental platform led by the radical liberals, but rather they shared several continuities, reflected in the decentralized system with respect to the financial burden of public education, the need and concern to promote a national and regional instructional system, and finally, the absence of a school culture present in working-class families.